EKSPLORASI PERSEPSI GURU SD TERHADAP PENGGUNAAN APLIKASI DIGITAL SEBAGAI MEDIA EVALUASI PEMBELAJARAN MATEMATIKA - Sifa Fatimah; Hendro Prasetyono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores elementary school teachers’ perceptions of using digital applications as an evaluation medium in mathematics learning. The research employed a qualitative approach through interviews and observations with teachers, students, and the principal to gain a deep understanding of the benefits, challenges, and implementation of digital applications in classroom evaluation. The findings revealed that teachers perceive digital applications as effective, interactive, and efficient tools that simplify the assessment process and enhance student motivation. Teachers highlighted that digital platforms enable quicker and more accurate evaluations, allowing real-time monitoring of students’ progress and providing instant feedback. Students reported that learning mathematics through digital applications is more engaging and enjoyable due to interactive features such as animations, quizzes, and feedback mechanisms. The principal emphasized that digital evaluation aligns with the school’s vision to integrate technology into learning, supported by training and adequate facilities. Despite minor challenges related to technical skills and digital literacy, the overall perception toward digital applications is positive. The use of digital applications not only improves evaluation efficiency but also promotes student independence, critical thinking, and digital competence. This research concludes that integrating digital technology in mathematics evaluation supports effective learning, modern education goals, and student readiness for the digital era. Keywords: Digital Application, Mathematics Learning, Evaluation, Teacher Perception, Digital Literacy